Surgical outcomes of various surgical approaches for transverse colon cancer - Hyo Jun Kim; Ji Won Park (Journal of Minimally Invasive Surgery)
The transverse colon has anatomical peculiarities in the middle position between the foregut and the midgut. Because the transverse colon harbors a flexure at both ends, mobilization of the transverse colon can be especially challenging compared with other colons. Although transverse colon cancer is relatively uncommon, an optimal surgical management for transverse colon cancer must be established. In transverse colon cancer, proximity to the pancreas and variation in arterial and venous anatomy make radical resection more difficult. Dissection of lymph nodes around the middle colic vessels is a critical step in transverse colon cancer resection. The proximity of the middle colic vessels to the superior mesenteric vessels contributes to the complexity of this step, making it challenging for less-trained surgeons. For these reasons, patients with transverse colon cancer were not included in most landmark studies that compared laparoscopic surgery with open surgery. More radical operations, such as subtotal colectomy or extended right or left hemicolectomy, can be performed for transverse colon cancer to secure an adequate lymphadenectomy. Such cancers have also been treated with limited segmental colectomies, such as right, transverse, or left colectomy. Currently, there is still a lack of standardized definitions and procedures. Therefore, it is time to discuss and establish optimal surgical treatments for transverse colon cancer.